Development of Komipa Media to Improve Students Scientific Thinking at MIS Al-Musthafawiyah - Siregar, Nurul Rizki Amalia; Anas, Nirwana; Lubis, Ramadan (Education Achievement: Journal of Science and Research, 2024)
The research entitled "Development of Komipa Media to Improve Students' Scientific Thinking at MIS AL-Musthafawiyah" was carried out by students who have scientific thinking in the field of Natural Sciences (Natural Sciences). This research shows that teachers use discovery in teaching materials. The aim of this research is to measure the development of students' scientific thinking by using comics as a learning medium. Previously, teachers used traditional media and rarely used comics. This research is an RND (Research and Development) study following the ADDIE model. The number of class III students at MIS Al-Mustafawiyah who took part was 18 people. Collection methods include questionnaires, interviews, and tests before (pretest) and after (posttest). The comic material assessment results show very high accuracy of up to 95%. In terms of language, the figure is 91.66%, which is also considered very important, and for media products it reaches 93.3% and in terms of design it gets a score of 80%.  Teachers' responses to the use of comics as a teaching medium show that comics are a very valid learning medium with a rating of 89.9%. Meanwhile, students' opinions on comics show that learning comics is very practical with a score of 89.2%. which will occur pre and post tests provide the most effective N growth of 86.7%. Based on research results, it is proven that komipa media is very easy and effective in improving students' science/scientific thinking skills at MIS Al-Mustafawiyah and is used by teachers as a solution, especially when the material changes the form of objects.